2008 ECSIS Symposium on Learning and Adaptive Behaviors for Robotic Systems (LAB-RS) 2008
DOI: 10.1109/lab-rs.2008.26
|View full text |Cite
|
Sign up to set email alerts
|

Mixture Model Segmentation for Gait Recognition

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In Field et al (2008a), it was shown that removing less abundant clusters from the GMM hinder identification of the activity and is detrimental to a stable centre of mass trajectory in possible robot motions. In Field et al (2008b), recognisable behaviour was segmented with a range of techniques and compared to subjective segmentations.…”
Section: Experimental Results In Human Motion Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Field et al (2008a), it was shown that removing less abundant clusters from the GMM hinder identification of the activity and is detrimental to a stable centre of mass trajectory in possible robot motions. In Field et al (2008b), recognisable behaviour was segmented with a range of techniques and compared to subjective segmentations.…”
Section: Experimental Results In Human Motion Recognitionmentioning
confidence: 99%
“…Current methodologies in handling the data are generally limited in their scope and application. There are promising and relatively new methods which may expedite future research outcomes including extensions on stochastic machine learning algorithms such as some hierarchical HMM (Kulic et al, 2008) topologies or restricted Boltzmann machines (Taylor and Hinton, 2009) and semi-supervised approaches (Field et al, 2008a;Zhou et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, motioning the induced symbolic patterns also provides a diagnostic ability guiding the often cyclic and interactive nature of applying machine learning in general. Previous other studies have validated this approach by combining together with unsupervised mixture modelling for gait recognition (Field et al, 2008) (Hesami et al, 2008). The premise of this proposed work is that all humans have, by the stage of adolescence (or maturity) developed various stylistic signatures or patterns of motion behaviour that can be typically (uniquely) associated with an individual.…”
Section: Wwwintechopencommentioning
confidence: 95%
“…Methodologies investigated to this point follow heuristic classifiers, Gaussian mixture models (GMM) [16], support vector machines [12], and hidden Markov model (HMM) [17,18]. However, those approaches consider a fixed number of human motions.…”
Section: Introductionmentioning
confidence: 99%